HEALTH RISK ASSESSMENT OF INHALATION EXPOSURE TO SO2 AND NO2 AMONG TRADERS IN A TRADITIONAL MARKET - Aria Gusti (Public Health of Indonesia)
Background: Air pollution is a global problem that is almost experienced by all countries. Causes of air pollution usually come from motor vehicles and industrial sources. One of places filled with transportations in community is a traditional market